Study on information sharing practices in supply chain: empirical evidence from manufacturing plants in Japan, Korea, Taiwan and Vietnam : Luận văn ThS. Kinh doanh: 603401 - Phung, Thi Xuan Huong (2019)
This thesis studies about information sharing practices in supply chain by manufacturing plants in 4 countries: Japan, Korea, Taiwan and Vietnam and their linkages with operational performance. Based on literature review, an analytical framework has been proposed to illustrate the linkages between 7 information sharing practices and 5 aspects of operational performance. Data for analysis in this study was retrieved from database of the international joint research initiative namely High Performance Manufacturing (HPM) project. This study use data collected from 103 manufacturing plants in three industries: automobile; electrical/electronics and machinery in Round 4 (2013-2015) of HPM project. Data was analyzed using oneway ANOVA and correlation analysis. The results indicate that Delivery, Quality and Demand information is most frequently shared among supply chain partners; Information sharing practices have positive linkages with aspects of operational performance although the linkages are different among countries. Practices of sharing Production and Inventory information are found to have positive linkages with all five aspects of operational performance. Besides addressing the gap in literature review about information sharing practices in supply chain among countries, this research also makes contribution by providing practical management implications for manufacturing plants to improve operational performance through appropriate implementation of information sharing practices with suppliers and customers in their supply chain. Keywords: Information sharing practices, Supply chain management, operational performance, High Performance Manufacturing (HPM).